ANALISIS JUMLAH SPARE AUXILIARY POWER UNIT APS3200 UNTUK ARMADA PT XYZ BERDASARKAN JUMLAH PESAWAT AIRBUS A320 – 200 - Radhix anang wahyudi; Ayu Martina; Freddy Franciscus (Jurnal Mahasiswa Dirgantara, 2026)
The Auxiliary Power Unit (APU) is a crucial component in commercial aircraft operations, primarily providing electrical power when the aircraft is not in operation. This study aims to determine the Mean Time Between Unscheduled Removal (MTBUR) of the APS3200 APU, estimate annual demand, and analyze the optimal spare quantity based on the fleet size of airline XYZ. The research methodology employs Weibull survival analysis using Minitab software to calculate MTBUR. Additionally, the estimation of spare unit requirements is based on MTBUR, annual demand, and re-supply time. The results indicate that the MTBUR of the APS3200 APU is 4,800 hours with a reliability level above 60%. Based on annual demand analysis, the recommended quantity for a fleet of 20 aircraft is 2 units per year. Furthermore, the recommended spare APU quantity varies depending on fleet size: 2 units for 20–30 aircraft, 3 units for 40–50 aircraft, 4 units for 60 aircraft, 5 units for 70–80 aircraft, and 6 units for 90 aircraft. These calculations allow airlines to optimize APU availability, enhance operational efficiency, ensure fleet reliability, and manage costs effectively within the aviation industry.